Improving the mechanical behavior of the adhesively bonded joints using RGO additive. (October 2016) - Marami, Gholamreza; Nazari, S. Adib; Faghidian, S. Ali; Vakili-Tahami, Farid; Etemadi, S.
Abstract: In this research, Araldite 2011 has been reinforced using different weight fractions of Reduced Graphene Oxide (RGO). Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) analyses were conducted and it has been shown that introduction of the RGO greatly changes the film morphology of the neat adhesive. Uni-axial tests were carried out to obtain the mechanical characteristics of the adhesive-RGO composites. It has been observed that introducing 0.5 wt% RGO enhances the ultimate tensile strength of the composites by 30%. In addition, single lap joints using neat adhesive and adhesive-RGO composites were fabricated to investigate the effect of the added RGO on the lap shear strength of the joints. Results show that the joints with added 0.5 wt RGO exhibited 27% higher lap shear strength compared to the joints bonded with neat adhesive. Finally, Finite Element (FE) numerical solutions using Cohesive Zone Modeling (CZM) have been carried out to simulate the failure behavior of the joints, and it has been shown that the FE models can predict the joint's failure load.